Transportation Model to Optimize Shipping Costs at PT Tiki Jalur Nugraha Ekakurir (JNE) Medan - Nasution, Fatwa Hillah; Br. Tarigan, Helpitaria; Hanum, Rizki Fadila; Tanjung, Ahmad Albar (PT Katersi Minar Permata, 2025)
This study aims to develop and analyze a transportation model to optimize the cost of shipping goods at PT Tiki Jalur Nugraha Ekakurir (JNE) Medan Branch Office which is driven by the challenges of cost management amidst the rapid growth of the logistics sector. The method used is a transportation model, specifically the initial solution approach North West Corner (NWC) and Vogel's Approximation Method (VAM), with the help of the POM QM application for Windows. The data processed includes the capacity of three large warehouses (gateways), namely Aceh, Kisaran, Pekanbaru and three small warehouses (dropcenters), namely Amplas, Gatot Subroto, Marelan, as well as the cost of shipping goods. The results of the initial allocation comparison show that both the NWC and VAM methods produce the same total transportation cost, namely Rp 5,477,900. However, this cost is not optimal. Furthermore, the calculation of the separate minimum driver wage using the Assignment Method resulted in a cost of Rp 578,000,- which is much lower than the total wage based on the NWC/VAM allocation of Rp 967,000,-. In conclusion, to achieve optimal operational cost efficiency, it is recommended that the allocation of goods distribution be integrated with the results of driver wage cost optimization.